Prevalence of psychiatric symptoms and associated factors in the adult population from the area affected by the tailings dam rupture - Brumadinho Health Project - Frederico Duarte Garcia; Maila de Castro Lourenço das Neves; Josélia Oliveira Araújo Firmo; Sérgio Viana Peixoto; Erico Castro-Costa (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To examine the prevalence of psychiatric symptoms and associated factors in the adult population of Brumadinho (MG), after the dam collapse. Methods: We included 2,740 participants with information about symptoms of post-traumatic stress disorder (PTSD), depression, anxiety, thoughts of death/self-harm, and poor sleep quality collected in 2021. Prevalence values of all conditions were estimated to compare the prevalence of psychiatric symptoms with the participants' sociodemographic characteristics and place of residence. Pearson's c2 test was used, with Rao Scott's correction. Crude and adjusted logistic regressions estimated odds ratios and 95% confidence intervals to assess the association between psychiatric symptoms and participants' characteristics. Results: The most common condition was depressive symptoms (29.3%), followed by post-traumatic stress symptoms (22.9%) and anxious symptoms (18.9%). Regarding the association between participants' characteristics in the adjusted analysis, being a female and living in a mining area was positively associated with symptoms of PTSD, depression, anxiety, thoughts of death/self-harm, and poor sleep quality. A positive association was also found between high school education and post-traumatic stress symptoms. In contrast a negative association was found between being aged ≥60 years and symptoms of PTSD, depression, and anxiety. Conclusion: High prevalence values were found for all psychiatric symptoms after the dam failure in Brumadinho. Being a female, living in the mining area, being ≥60 years old, and having an educational level were all associated with the psychiatric symptoms investigated.